Biomass and Carbon Stock Estimation Inventory of Indonesian Bananas (Musa spp.) and Its Potential Role for Land Rehabilitation - Danarto, Setyawan Agung; Hapsari, Lia (BIOTROPIA, 2016)
<!--[if gte mso 9]> <![endif]--> ABSTRACT Bananas (Musa spp.) are widely cultivated in Indonesia. They are extensively grown in backyards, homegardens, intercropped with short term crops and also in agroforestry system. Potential role of bananas to absorb and store Carbon related to climate change mitigation is rarely studied. An inventory of biomass and C-stock estimation on banana accessions has been conducted in Musa germplasm plots - Purwodadi Botanic Garden, Pasuruan. 42individual banana accessions has been estimated its biomass and C-stock comprises of 5 wild types and 37 cultivars. Biomass estimated using non-destructive method ie. allometric equation for banana by measuring its mature stage pseudostem diameter at breast height (dbh). C-stockwas estimated by crossing its biomass to averaged value of banana C-stock 0,46.The results showed that the biomass and C-stock estimation level were in positive correlations with its plants pseudostem dbH. The conclusions of these research that Kepok Bung cultivar has the highest level of estimated biomass and Carbon stock about 15, 02 kg/plant and 6, 92 kg C/plant and then cultivars with range averaged C-stock between 3,5 – 3,9 kg C/plant (higher level) are Tlekung, Baflo, and Cici. Musa balbisiana species contributes higher level of biomass and C-stock estimation than Musa acuminata species. Keywords: Banana, biomass, carbon stock (C-stock), estimation, Musa, non- destructive, Purwodadi Botanic Garden <!--[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->